Asymmetric Synthesis of 2-Arylethylamines: 2025. An Updated Review - García-González, Ángel; Manchado, Alejandro; Riesco, Pablo; Nieto, Carlos T.; Díez, David; Garrido, Narciso M. (SynOpen, 2025)
2-Arylethylamines are present in several natural bioactive compounds, as well as in many nitrogen-containing drugs. Their ability to cross the blood–brain barrier makes this family of compounds of special interest in medicinal chemistry. Asymmetric methodologies towards the synthesis of 2-arylethylamine motifs are of significant interest due to the challenges they present. In this graphical review, we highlight recent advances in the metal-free and metal-catalyzed asymmetric synthesis of 2-arylethylamines, covering the literature published in 2025 (up until late October). We showcase the different methodologies towards the aforementioned motif, including chiral induction, organocatalysis, organophotocatalysis and enzymatic catalysis.
Keywords: 2-phenethylamines; 2-arylethylamines; asymmetric synthesis; chiral induction; organocatalysis; organophotocatalysis; enzymatic catalysis; metal catalysis